Theoretical and practical issues of researching the characteristics of the formation of social tolerance in students (Journal of Pedagogical Inventions and Practices, 2023)
This article provides information about the concept of tolerance and empathy, the ideas of tolerance, the development of a sense of tolerance, modern approaches to empathy, and the concept of the differentiation of the phenomenon of tolerance.